DEVELOPMENT MODEL OF DIGITAL CITIZENSHIP OF SECONDARY SCHOOL TEACHER UNDER A JURISDICTION OF BANGKOK METROPOLITAN - Pumswad, Orasa; Kawmongkon, Songyos; Dechome, Patchara (Journal of MCU Nakhondhat, 2024)
This research aimed to 1) Create a model for developing digital citizenship in teachers. The informants were 10 experts, using purposive selection. The instrument used was an assessment. The statistics used were mean and standard deviation, and 2) Testing and evaluating the digital citizenship development model for teachers. The target group included school administrators and teachers of Wat Sutharam Secondary School, totaling 63 people. The tools used were tests and assessments. The statistics used included means, standard deviations, test scores compared to criteria, and relative development scores. The research results found that: 1) The model for developing digital citizenship for secondary school teachers under a jurisdiction of Bangkok is called the "2P2S6D Model" consisting of planning, teacher development with the Professional Learning Community, supervision, or monitoring and evaluation. (Supervision) and constant improvement (Steady Improvement). There are 6 areas of digital citizenship that must be developed: 1) Digital literacy (Digital Literacy) 2) Access to digital technology media (Digital) Access) 3) Communication with digital technology (Digital Communication) 4) Respect for the law and the rights of oneself and others (Digital Law) 5) Use of digital technology safely (Digital Security) and 6) Commercial transactions through Digital (Digital Commerce), and 2) Results of suitability assessment Feasibility, validity, and usability of the digital citizenship development model in every aspect and the overall picture is at the highest level. The overall test results passed the criteria at 87.6% and the overall development assessment results were at a high level.